An Investigation on the Opinions of Class and Guidance Teachers About the Challenges in Mainstream Education - Tevhide Kargın; Atlas Bogenç; Elvan Baran Karalar (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
Introduction: One of the most important factors in mainstreaming practices is the teacher. The role of the created class and psychological guidance, such as ensuring social cohesion between students with special educational needs and their peers, and the active inclusion of families throughout their life, cannot be denied. It is expected that the opinions and expectations regarding the inclusion difficulties and experiences of the classroom and guidance teachers working in primary schools in the province of Istanbul are reached.Method: In the study in which the case study model, which is one of the qualitative research methods, was used; semi-structured interviews were conducted with seven classroom teachers who have inclusion students in their classroom and six psychological counselor/guidance teachers who have inclusion students in their school. By applying content analysis to the data obtained from the interviews, the main themes and sub-themes were formed and the findings were reached.Findings: Research findings show that classroom teachers prepare the individualized education program (IEP) with the help of the guidance teacher. The school administration does not have enough information about the inclusion practice because the classrooms are crowded. Thus the teachers have difficulty in gaining academic skills, as well as finding and adapting appropriate materials for mainstreaming students. Counselors, on the other hand, state that the IEP development unit remains on paper, that all responsibilities related to IEP are assigned to them, and that the school administration does not cooperate on inclusion. In addition, both classroom teachers and guidance teachers stated that the communication and cooperation they established with the institutions where the student received support education was one-sided and they did not receive any feedback regarding the student. The fact that families do not accept their children's inadequacy, and do not have enough information about inclusion, is another finding that makes cooperation difficult for classroom and guidance teachers.Discussion: The findings obtained from the research revealed the necessity of the classroom and guidance teachers to be in cooperation with the school, family and stakeholders who provide support education to the students in the inclusive practice. This cooperation will enable the student's educational process to improve their learning better. It is recommended to conduct experimental studies based on school-family cooperation in similar studies.